An ultra-broadband microstrip antenna using a triple dumbbell-shaped defected ground structure - Haryanto, Puji; Astuti, Dian Widi; Alaydrus, Mudrik; Firdausi, Ahmad; Rusdiyanto, Dian; A Majid, Huda (Universitas Mercu Buana, 2026)
Microstrip antennas are widely used in modern communication systems due to their compact size and low profile. However, they typically suffer from narrow bandwidth, limiting their performance in advanced wireless applications. This study addresses this limitation by employing a triple dumbbell-shaped defected ground structure (DGS). The antenna is designed to operate at 3.5 GHz using a Rogers RT5880 substrate, and its performance was analyzed through simulations in HFSS 15.0 software. Without the DGS, the antenna exhibits a fractional bandwidth (FBW) of only 1.71%, operating from 3.47 GHz to 3.53 GHz. Incorporating the triple dumbbell-shaped DGS in the ground layer increases the FBW significantly to 53.6%, extending the operating frequency range from 2.39 GHz to 4.14 GHz. This improvement was achieved through the careful optimization of DGS parameters. The simulated gain at 3.5 GHz is 5.13 dBi. The proposed design demonstrates superior performance compared to conventional techniques such as split-ring resonators (SRR) and Butler matrix (BM) configurations. Simulation and measurement results show excellent agreement, validating the design. The achieved ultra-wideband performance benefits 5G and next-generation systems, offering greater frequency tolerance, diverse signal support, increased capacity, and reliable operation, making the antenna a promising candidate for future wireless applications.